Modernization of Islamic Boarding School Infrastructure Through Community Empowerment in Batu City (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Formal education based on religious values is one of the most significant foundations for building a strong nation. The Ar-Razi Islamic Boarding School is envisioned as an integrated educational institution that combines the traditional pesantren system with formal schooling. Strategically located in Bulukerto Village, Batu City, the school benefits from a natural mountainous setting, providing a serene and conducive learning environment.This community-based design project aims to develop a comprehensive and context-sensitive master plan that responds to the client’s vision. The key objectives include accommodating both male and female students in a spatially organized manner, designing inclusive and functional facilities such as classrooms, dormitories, a central masjid, administrative areas, and outdoor activity zones for archery and horseback riding, while also preserving green open spaces for ecological and recreational purposes. The planning and design process was conducted in four main stages: (1) coordination stage to align visions and understand partner needs, (2) preliminary study through field surveys and community engagement, (3) master plan development focusing on zoning and infrastructure layout, and (4) evaluation and finalization with stakeholders. This participatory approach involved close collaboration with pesantren owners, local residents, and village officials to ensure the final design reflects both cultural values and future development goals. The resulting master plan not only meets the immediate spatial and functional needs of the pesantren but also lays the foundation for a sustainable and value-based educational environment that will nurture future generations of Islamic learners and leaders